2008
DOI: 10.1194/jlr.m700410-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Lystbeige mutation is atheroprotective in chow-fed apolipoprotein E-deficient mice

Abstract: Lyst beige mice crossed with hyperlipidemic low density lipoprotein receptor-deficient mice (BgLDLr 2/2 ) display increased lesion area and a more stable lesion morphology. To verify that the beige phenotype is not unique to LDLr 2/2 mice, we examined atherosclerosis in beige, apolipoprotein E-deficient mutant mice (BgApoE 2/2 ). Severe diet-induced hyperlipidemia in BgApoE 2/2 mice resulted in increased aortic sinus lesion areas compared with controls. Minimal aortic lesions were observed in both genotypes on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, more recent studies indicate that this atheroprotective effect is dependent on the presence of the beige mutation in bone marrowderived cells, endothelial cells, and vascular smooth muscle cells. 30 In the present study, we avoided such complexities by directly demonstrating that NK cells promote atherosclerosis. Specific depletion of NK cells by the anti-Asialo-GM1 antibody attenuated atherosclerosis consistent with NK cells augmenting development of atherosclerosis; other lymphocyte populations including NKT cells were unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies indicate that this atheroprotective effect is dependent on the presence of the beige mutation in bone marrowderived cells, endothelial cells, and vascular smooth muscle cells. 30 In the present study, we avoided such complexities by directly demonstrating that NK cells promote atherosclerosis. Specific depletion of NK cells by the anti-Asialo-GM1 antibody attenuated atherosclerosis consistent with NK cells augmenting development of atherosclerosis; other lymphocyte populations including NKT cells were unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Beige mutation, which involves the Lyst gene encoding a protein implicated in lysosomal trafficking, results in a complicated phenotype that goes beyond decreased NK cell activity 13 , 14 . Defects in cell function may include, in addition to NK cells, neutrophils, macrophages, or smooth muscle cells (SMCs) 15 , making it unclear whether the increase in atherosclerosis in Lyst beige xLdlr -/-mice was a consequence of defective NK cell function. Subsequently, different results were observed using a Ly49A transgenic mouse model of NK cell deficiency 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these strategies could not exclude the role of other lymphocytes in the development of atherosclerosis (76). For example, beige mutant mice also include defects in neutrophils, macrophages, or smooth muscle cells (77); in Ly49A transgenic mice, the role of natural killer T cells (NKT) and CD8 subsets, whose functions are influenced by Ly49A, were not considered (78,79); GM1 is also expressed by myeloid cells, epithelial cells, and T cell subsets, and so on (80)(81)(82)(83). A recent study, by using Ncr1 iCre/+ R26 lsl−DTA/+ mice that specially deplete NK cells and Noémice in which NK cells are hyperresponsive, demonstrated that NK cells showed no direct effect on the natural development of hypercholesterolemia-induced atherosclerosis.…”
Section: Nk Cells In Atherosclerosismentioning
confidence: 99%